Analyzing commons: complex dynamics leading to sustainably governed urban commons - Müller, Agnes Katharina; Köpper, Julia (Frontiers in Sustainable Cities, 2023)
Urban commons as concept offer new perspectives of collaborative urban design and a participatory management of urban resources. In many cases, citizens create urban commons as bottom-up initiatives, although they often are cooperating with local governments or private proprietors, particularly if a long-term perspective is targeted for their project. Urban commons therefore shed light on the tension between bottom-up initiatives and the public and private sector in urban governance. This article investigates how the interrelation of different variables, such as implementation process, accessibility of the community, ownership structure among others help to constitute sustainable governed commons, based on three case studies in different urban settings. The following aspects are highlighted: how and under which conditions the co-relation of different variables can constitute a sustainable urban commons governance. The specific strategies of the different commons are explored through the overarching categories of scale, permeability, and organisation. Each case study is evaluated in terms of sustainable governance by identifying enhancing or constraining variables, external conditions and internal challenges. By comparing the different examples, the limits and possibilities of sustainable urban commons governance are reflected.